2007
DOI: 10.1007/s11738-007-0064-z
|View full text |Cite
|
Sign up to set email alerts
|

Flooding-induced changes in photosynthesis and oxidative status in maize plants

Abstract: Maize plants (Zea mays L.) were subjected to soil flooding for 72, 96, and 120 h. A noticeable decrease in the rate of net photosynthesis (P N ) and the activity of ribulose-1,5-bisphosphate carboxylase (RuBPC, EC 4.1.1.39) were observed. The values of intercellular CO 2 concentrations (c i ) increased in all flooded plants without significant changes in stomatal conductance (g s ). The activity of phosphoenolpyruvate carboxylase (PEPC, EC 4.1.1.31) increased twofold 120 h after soil flooding. Flooding of maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
81
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 34 publications
14
81
0
5
Order By: Relevance
“…The decrease in carboxylation efficiency may occur due to lower carboxylase RuBisCO activity in plants under flood conditions (YORDANOVA;POPOVA, 2007). In addition, the accumulation of photoassimilates in the leaves caused by the reduction in the phloem sap flow in flooded castor bean plants (PEUKE et al, 2014) can result in the feedback inhibition of photosynthesis (STITT, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in carboxylation efficiency may occur due to lower carboxylase RuBisCO activity in plants under flood conditions (YORDANOVA;POPOVA, 2007). In addition, the accumulation of photoassimilates in the leaves caused by the reduction in the phloem sap flow in flooded castor bean plants (PEUKE et al, 2014) can result in the feedback inhibition of photosynthesis (STITT, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the concentrations of hydrogen peroxide and MDA in roots and leaves of various plants exposed to soil flooding was repeatedly demonstrated (Asada, 2006) and the existence of a direct relationship between stress sensitivity and the early accumulation of MDA was shown (Arbona et al, 2008). Usually soil hypoxia increased the MDA concentration, especially in intolerant species (Chen and Qualls, 2003;Yordanova and Popova, 2007). In our experiments the TBARs concentration increased and then remained at a high level in roots of flooded spring rape but in the leaves an initial increase in the TBARs concentration changed to a decrease at the end of the experiment.…”
Section: Fig 1 Alcohol Dehydrogenase (Adh) Activity In Roots Ofmentioning
confidence: 97%
“…According to different authors the proline accumulation in plant should be considered as one of the links of the common chain of biochemical adaptation mechanisms functioning in stressed plants (Radyukina et al, 2008;Shevyakova et al, 2009). Some reports showed an increase in proline concentration in plants under soil flooding (Yordanova and Popova, 2007). It was found that, under the waterlogging conditions, the number of new leaves, root length, plant height and plant biomass and content of soluble protein in roots of Malus species declined, while the content of malondialdehyde (MDA) and proline, the generation rate of superoxide radical, relative membrane permeability, and the activities of SOD and peroxidase in roots significantly increased (Bai et al,2008).…”
Section: Introductionmentioning
confidence: 99%
“…Uma das consequências do alagamento do solo é a baixa atividade fotossintética, causando diminuição da concentração de clorofila (LADYGIN, 2004;YORDANOVA;PAPOVA, 2007), resultando na formação de clorose. Trabalhando com ervilha, Ladygin (2004) constatou em plantas que passaram por períodos de hipóxia radicular, as folhas apresentaram uma coloração amarela à quase branca, resultado da pequena quantidade dos pigmentos contidos nos cloroplastos, o que acarretou uma baixa taxa fotossintética.…”
Section: Introductionunclassified